Analisis Perbandingan Portofolio Optimal Single Index Model dan Metode CATM Menggunakan Indeks Pengukur Sharpe, Treynor, dan Jensen (Studi Kasus Saham Jakarta Islamic Index) Pada Masa Pandemi Covid 19 - Yuyun Septia Rodita; Media Rosha (UNIVERSITAS NEGERI PADANG, 2022)
Investment is the investment of funds to earn profits in the future. The higher the expected rate of return, the higher the risk that will be faced. To minimize the level of risk and maximize the rate of return, an optimal portfolio is formed. The models that can be used to form an optimal portfolio are the Single Index Model and the Capital Asset Pricing Model (CAPM). This study aims to analyze the comparison of the optimal portfolio of Jakarta Islamic Index shares during the Covid-19 pandemic with the Single Index Model and CAPM and to measure the optimal portfolio performance formed by measuring indexes, namely Sharpe, Treynor, and Jensen. Based on the analysis of the optimal portfolio performance measurement shows that the optimal portfolio formed by the CAPM method has a better performance than the Single Index Model.